Sense and the city: An emotion data framework for smart city governance - Katharine S. *ca. 20. Jh.* Willis; Christian Nold (Journal of Urban Management, 2022)
In the smart city agenda, data plays a key role in shaping governance and participation around urban planning, and this data is increasingly derived from sensors of all kinds. These sensors increasingly include physiological and sentiment analysis to gauge the emotional states of urban citizens. In urban planning, emotional data has so far been conceptualised as "people as sensors" where data is used to create an aggregated emotion layer for real-time urban planning. This paper argues this approach does not enable citizens any meaningful participation in urban planning. In contrast, this paper demonstrates what emotion can "do" when citizen actively use emotions to participate in the problem framing in smart city governance. The paper offers a framework of smart city participation with emotion data by focusing on the Bio Mapping project, where physiological sensors are used as participatory mapping approach that led to urban planning. This approach enabled citizens to engage in a dialogue around their emotional response to urban space and articulate the potential for emotion data in urban governance. There needs to be a consideration of 1) multi-dimensional emotion data, 2) an active participant role, 3) extended participation within the planning process 4), and empowerment within urban governance. The paper argues that a participatory approach to emotion data can function as a dynamic leverage point of negotiation in smart city governance between citizens, urban space, and civic agencies.
Keywords: 710; Emotion data; Bio sensing; Participation; Urban planning; Smart cities; Governance